Expression of selected microRNAs in pancreatic ductal adenocarcinoma: is there a relation to tumor morphology, progression and patient's outcome? - Szabo, A; Gurlich, R; Liberko, M; Soumarova, R; Vernerova, Z; Mandys, V; Popov, A (Neoplasma, 2020)
Pancreatic ductal adenocarcinoma (PDAC) remains a disease with extremely poor prognosis and limited effective available treatment. Differential expression of miRNAs isolated from tumor tissue has been proposed as a marker for tumor diagnosis, progression, and prognosis. Nevertheless, the prognostic value of miRNAs expression in PDACs for patient outcome still remains unclear. Expression of 7 selected miRNAs, isolated from FFPE samples of 54 PDAC patients, was quantified using RT-qPCR. The relationship of miRNA expression levels with tumor histology, clinicopathological characteristics, patient overall survival (OS), and progress-free survival (PFS), was subsequently evaluated. Overexpression of miR-21, miR-155, and miR-210 was observed in PDACs (up to 72.62, 232.36, and 181.38-fold, respectively), in comparison with non-neoplastic tissues. On the other hand, miR-96 and miR-217 were significantly downregulated in PDACs (up to one hundred times). No differences were, however, noticed between cancer and normal tissues for the expression levels of miR-148a and miR-196a. On the other hand, expression levels of all 7 miRNAs failed to demonstrate a significant correlation with parameters of tumor progression, such as tumor stage, grade, nodal involvement, perineural, and vascular invasion. The positive correlation of miR-210 levels was, however, observed with patient age (ρ=0.35). Additionally, miR-148a and miR-217 expressions have shown a positive association with tubular tumor growth pattern (ρ=0.39; ρ=0.28). The negative correlation of miR-148a values was also demonstrated with dissociative growth pattern and nuclear atypia (ρ=-0.30; ρ=-0.27). Finally, no statistically significant correlation could be demonstrated with the expression levels of all 7 tested miRNAs and PDAC patient survival; neither for OS nor for PFS (p>0.05). Our data have confirmed abnormal miRNAs expression in PDACs in comparison with adjacent non-neoplastic tissue. On the other hand, no correlation was discovered between miRNA expression and parameters of tumor progression. We have found a significant association between histologic tumor growth patterns and miRNA expression, making this work the first study, which analyses this aspect of PDAC. Finally, in our group of patients, no relationship of miRNA levels and patient prognosis could be demonstrated. Therefore, further investigation is required to evaluate the predictive and prognostic potential of miRNAs in a clinical setting.
Keywords: duktální karcinom slinivky břišní; prognóza; Pancreatic Neoplasms; mikro RNA; Gene Expression Regulation, Neoplastic; regulace genové exprese u nádorů; Prognosis; Carcinoma, Pancreatic Ductal; MicroRNAs; lidé; Biomarkers, Tumor; Humans; nádorové biomarkery; nádory slinivky břišní